A Domino Approach for the Synthesis of α‐Iodo‐β‐dicarbonyl Compounds from α‐Epoxycarbonyls. Issue 22 (1st August 2017) - Mahato, Sachinta; Chatterjee, Rana; Santra, Sougata; Zyryanov, Grigory V.; Hajra, Alakananda; Majee, Adinath
Abstract: A series of α ‐iodo‐ β ‐dicarbonyl compounds have been synthesized from α ‐epoxycarbonyl compounds through a consecutive reaction by ring opening of epoxide followed by the oxidation in presence of NH2 OH⋅HCl and NaIO4 . To the best of our knowledge, this is the first time report for the use of α ‐epoxycarbonyls as a key starting material for the synthesis of α ‐iodo‐ β ‐dicarbonyl compounds. Various functional groups are well tolerated under the present reaction conditions. The epoxy carbonyl compound containing alkyl part is also effective for this conversion. The reactions were carried out in open atmosphere and are not sensitive to air and moisture. All of the synthesized compounds have been characterized by spectral and analytical data. The potential synthetic applicability of this method was investigated on a gram scale using the model reaction. The advantages of the present method are operational simplicity, short reaction time, general applicability, good tolerance to scale‐up synthesis, as well as readily available reagents. A plausible mechanism has been proposed on the basis of an intermediate isolated from the reaction mixture. Abstract : First approach for the synthesis of α ‐iodo‐ β ‐dicarbonyl compounds from α ‐epoxycarbonyls was developed. Various functional groups are well tolerated under the present reaction conditions. The potential synthetic applicability of this method was investigated on a gram scale using the model reaction. The advantages of the present method are operational simplicity, short reaction time, general applicability, good tolerance to scale‐up synthesis, as well as readily available reagents.